Young, Simon y Ermacora, Davide (2024) (eds.): The Exeter Companion to Fairies, Nereids, Trolls and Other Social Supernatural Beings, Exeter, University of Exeter, 260 pp. - Abenójar, Óscar (Boletín de Literatura Oral, 2025)
Reseña